Quantification of three macrolide antibiotics in pharmaceutical lots by HPLC: Development, validation and application to a simultaneous separation - A Mahmoudi; Silvia De Francia; Mohamed Salah Boukhechem; Elisa Pirro (University of Huddersfield Press, 2016)
A new validated high performance liquid chromatographic (HPLC) method with rapid analysis time and high efficiency, for the analysis of erythromycin, azithromycin and spiramycin, under isocratic conditions with ODB RP18 as a stationary phase is described. Using an eluent composed of acetonitrile -2-methyl-2-propanol -hydrogenphosphate buffer, pH 6.5, with 1.5% triethylamine (33:7: up to 100, v/v/v), delivered at a flow-rate of 1.0 mL min-1. Ultra Violet (UV) detection is performed at 210 nm. The selectivity is satisfactory enough and no problematic interfering peaks are observed. The procedure is quantitatively characterized and repeatability, linearity, detection and quantification limits are very satisfactory. The method is applied successfully for the assay of the studied drugs in pharmaceutical dosage forms as tablets and powder for oral suspension. Recovery experiments revealed recovery of 97.13-100.28%.